2017
DOI: 10.1007/978-3-319-61425-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Constructive Video-Based Learning: Requirements Elicitation from Exploratory Studies

Abstract: Abstract. Although videos are a highly popular digital medium for learning, video watching can be a passive activity and results in limited learning. This calls for interactive means to support engagement and active video watching. However, there is limited insight into what engagement challenges have to be overcome and what intelligent features are needed. This paper presents an empirical way to elicit requirements for innovative functionality to support constructive video-based learning. We present two user … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…Earlier work in AVW-Space indicated that constructive learners who wrote comments while watching videos were more likely to increase their knowledge [11,12]. This paper explores the relationship between diversity patterns and video usage for learning.…”
Section: Case Study -Comments On Videos For Learningmentioning
confidence: 99%
“…Earlier work in AVW-Space indicated that constructive learners who wrote comments while watching videos were more likely to increase their knowledge [11,12]. This paper explores the relationship between diversity patterns and video usage for learning.…”
Section: Case Study -Comments On Videos For Learningmentioning
confidence: 99%
“…The ratings, which are designed to further promote reflection, are: "This is useful for me", "I hadn't thought of this", "I didn't notice this", "I don't agree with this", and "I like this point". Two AVW studies were conducted in March and July 2016 with postgraduates and undergraduates respectively, focusing on pitch presentations [34,35]. The studies examined whether learning was happening and what kind of interactions contributed to learning.…”
Section: Active Video Watching Approachmentioning
confidence: 99%
“…Our research adopts interactive note-taking in video watching for soft skill learning. Previous studies found that the approach is effective only when the students actively engage with video content [34] and requirements are gathered for interactive personalised nudges to promote desired learning behaviour [35]: assist students noticing important points in videos, linking video snippets to aspects related to soft skill learning (e.g. recognise key skill elements, contextualise in past and future experience) and broadening soft skill learning portfolio (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we developed AVW-Space, a controlled platform for informal video-based learning through note-taking where students watch and comment on videos [21]. Several studies using AVW-Space with undergraduate and postgraduate university students in the context of presentation skills have shown that students who write comments instead of passively watching improve their understanding of presentation skills.…”
Section: Introductionmentioning
confidence: 99%
“…Gathering requirements for the effectiveness of AVW-Space in an earlier study indicated the need to encourage student commenting, which was positively correlated with conceptual learning, while at the same time preserving students' freedom to interact with videos in a way they prefer [21]. This informed the extending of AVW-Space by adding nudges [11] -interventions that influence people's behavior to make beneficial choices (paternalism) in a non-compulsory manner (libertarian).…”
Section: Introductionmentioning
confidence: 99%